PENGEMBANGAN BAHAN AJAR LKS DALAM PROSES BELAJAR MENGAJAR PENJASORKES BAGI SISWA KELAS V DI SD ISLAM TA’ALLUMUL HUDA KECAMATAN BUMIAYU TAHUN PELAJARAN TAHUN AJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study is to produce a product development of teaching materials worksheets in teaching and learning for students of class V in SD Islam Ta’allumul Huda District Bumiayu. This research is a Research and Development (R & D). The research method used is the research development of teaching materials worksheets Penjasorkes fifth grade 2nd semester. Research data in the form of sheets of evaluation regarding the quality of products, suggestions for improvement of the product, and the results of the questionnaire students. Technique data analysis which used is descriptions the percentage and descriptions qualitative for uncover aspects of the effectiveness LKS against teaching and learning process. From the test results obtained evaluation data of experts penjas I obtain the value of 3.12 with the criterion LKS (Decent), expert penjas II scored 3.35 with criteria LKS (Decent), learning experts scored 3 criteria LKS (Very Worthy) , small group try to obtain the results of 87.75% with criteria of student responses (Very Strong), and field trials to obtain the results of 90% with criteria of student responses (Very Strong) as well as the analysis of the level of effectiveness of LKS Penjasorkes tehadap learning process to obtain an increase of 6,97%. Conclusion of this research is that the product development of teaching materials LKS in the process of learning teaching and for students of classes V in SD Islam Ta’allumul Huda District Bumiayu very effective.